Structural Reforms in Latin America: What Has Been Reformed and How to Measure It - Eduardo Lora (Inter-American Development Bank, Research Department, 2001)
Since the mid-1980s a profound change of direction in the structural policies of the region has taken place. The development model based on protecting national markets and state intervention was replaced by a set of policies aimed primarily at seeking to improve efficiency, facilitate the operation of markets, and reduce the distorting effects of state intervention in economic activities. An earlier version of this article (Lora, 1997) was prompted by the absence up to that time of measurements of progress in reforms. As was then argued, the lack of direct measurements of structural policies had stood in the way of adequately evaluating the effects of the reforms on economic growth and other variables. The few studies that had attempted to analyze the effects of the reforms had used result variables, such as the foreign trade ratio of the economy, or the size of public spending, or financial depth, rather than policy variables, such as tariffs, tax rates, or reserve requirement ratios. The indices of reform that were proposed at that time served as the basis for various studies that analyzed the effects of the reforms and stimulated the construction of other reform indicators.
Keywords: 330; Wirtschaftsreform; Strukturpolitik; Handelsliberalisierung; Finanzmarktregulierung; Steuerreform; Privatisierung; Arbeitsmarktflexibilität; Lateinamerika